Utilization Of Statcom Control For Fsig-Based Wind Forms Under Asymmetrical Grid Faults (International Journal of Engineering and Computer Science, 2014)
The stability of fixed-speed induction generator (FSIG)-based wind turbines can be improved by a StatCom, which is well known and documented in the literature for balanced grid voltage dips. Under unbalanced grid voltage dips, the negative-sequence voltage causes heavy generator torque oscillations that reduce the lifetime of the drive train. In this paper, investigations on an FSIG-based wind farm in combination with a StatCom under unbalanced grid voltage fault are carried out by means of theory, simulations, and measurements. A StatCom control structure with the capability to coordinate the control between the positive and the negative sequence of the grid voltage is proposed. The results clarify the effect of the positive- and the negative-sequence voltage compensation by a StatCom on the operation of the FSIG-based wind farm. With first priority, the StatCom ensures the maximum fault-ride-through enhancement of the wind farm by compensating the positive-sequence voltage. The remaining StatCom current capability of the StatCom is con-trolled to compensate the negative-sequence voltage, in order to reduce the torque oscillations. The theoretical analyses are verified by simulations and measurement results on a 22-kW laboratory setup.